Teaching social work students using a person-centered ethics of care model approach to working with individuals with intellectual/developmental disabilities and their caregivers. - Alford, Sabretta; Son, Esther (Social Work Education, 2026)
The field of intellectual and/or developmental disabilities (I/DD) can encompass many conditions affecting the growth and maturation of children, including seizures, cerebral palsy, Down syndrome, traumatic brain injury, autism spectrum disorders, and others. Theoretical models that focus solely on the impact of physical disability are not always appropriate for individuals with I/DD. Individuals with I/DD are quickly sidelined in mainstream disability research and practice since these children have complex needs affecting them physically, cognitively, and/or behaviorally. The responsibility for lifelong assistance often falls on the caregiver to balance the challenges of caring for a severely disabled child across the lifespan. This paper discusses a model of care that places the individual with intellectual and developmental disabilities (I/DD) at the center of numerous forces shaping their development, including educational, medical, governmental, financial, and social service components. The Person-Centered Ethics of Care (PC-EoC) model described here illustrates the complex and interactive needs of individuals with intellectual and developmental disabilities (I/DD) and their caregivers. This paper focuses on educating social work students using the model to work with individuals with intellectual and developmental disabilities (I/DD).